KESADARAN UMAT PAROKI SANTO MIKHAEL KADA KEUSKUPAN ATAMBUA TENTANG MAKNA EKARISTI HARI MINGGU DALAM TERANG HUKUM III DEKALOG - Abel, Selviana Gisela Abel; Tamelab, Petrus; Duka, Gerardus B. (STIPAS Keuskupan Agung Kupang, 2020)
The fundamental reason for the researchers choosing this title is: the reality of the lack of awareness of the people about Sunday's eucharist at the Santo Michael Parish Church. A Christians have not understood the importance of the eucharist in everyday life. The Eucharist is very important in the life of the ummah as the source and peak of the whole human life (PUMR 16). Why is that? Because there is salvation that comes from God. The formulation of the problem to be raised is the extent to which the understanding and awareness of the people in the parish of Saint Michael Kada with factors that support and hinder people's understanding and solutions to overcome them. The purpose of the research is to answer the formulation of the problem presented. The foundation of the theory developed is an explanation of concepts and theories relating to the Eucharist. Also uses Biblical and theological fundamentals about the Eucharist. The hypothesis that was built in this study was that the people did not understand the Eucharist culminating on Sundays, and the efforts that would be made by means of socialization and policies made by the Parish Priest. The research method used in this study is naturalistic descriptive. Naturalistic is another name for qualitative methods which refers to the description of the natural situation of the people and the presentation of data that is data analysis. Descriptive refers to the level of explanation or process to explain something. The location of this study is the Santo Michael Parish Church, to support the efficiency and effectiveness of research. The instruments of this study were parish priest, 2 catechists, 1 DPP and 3 people as data sources. Data collection techniques used in this study were observation, interviews and documentation. The technique of testing the validity of the data is by extending observations and increasing perseverance. Data analysis techniques are data collection, data reduction, data presentation and conclusion drawing. The results of the study and discussion of the title above are based on research that is located in the Santo Michael Parish of Kada approximately one month. Data sources were 7 people including the parish priest. Questions given to informants amounted to 11 questions to answer the problem formulation. As for the problems found in the participation of the people in attending the Eucharistic celebration on Sunday, most of the Kada parishioners did not attend the Eucharistic celebration on Sundays, it was caused by some people who did not understand the meaning of the Eucharist on Sunday so they preferred trading on the market. Seeing this problem there are efforts made, namely by giving the Catechesis of faith, increasing pastoral visits and pastoral policies from the parish